2016
DOI: 10.2147/tcrm.s112236
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the effect of sodium glucose cotransporter 2 inhibitor monotherapy on glycemic and other clinical laboratory parameters in type 2 diabetes patients

Abstract: ObjectivesWe aimed to determine the effect of sodium glucose cotransporter 2 (SGLT2) inhibitor monotherapy on glycemic and other clinical laboratory parameters versus other antidiabetic medications or placebo therapy in patients with type 2 diabetes mellitus. In addition, we aimed to investigate the risk of diabetic ketoacidosis associated with SGLT2 inhibitor therapy and evaluate its weight-sparing ability.DesignMeta-analysis.Materials and methodsPubMed and MEDLINE were searched to identify eligible studies u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
(133 reference statements)
2
18
0
Order By: Relevance
“…In patients with obesity, licogliflozin was associated with a 5.7% reduction in placebo-adjusted body weight following 12 weeks of treatment. This is in contrast to the 1%-2% reduction in weight that was observed over 12 weeks of treatment with selective SGLT2 inhibition, 37 and it is in line with the clinically meaningful weight loss of >5% (at 12 months) that is required by the FDA for approval of new drugs. 8 FDA analysis of clinical trial data revealed that a 12-week weight loss of >5% achieved with lorcaserin of phenterminetopiramate was predictive of meaningful weight loss at 12 months following treatment, 38 suggesting that the weight loss seen with licogliflozin by 12 weeks is promising.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In patients with obesity, licogliflozin was associated with a 5.7% reduction in placebo-adjusted body weight following 12 weeks of treatment. This is in contrast to the 1%-2% reduction in weight that was observed over 12 weeks of treatment with selective SGLT2 inhibition, 37 and it is in line with the clinically meaningful weight loss of >5% (at 12 months) that is required by the FDA for approval of new drugs. 8 FDA analysis of clinical trial data revealed that a 12-week weight loss of >5% achieved with lorcaserin of phenterminetopiramate was predictive of meaningful weight loss at 12 months following treatment, 38 suggesting that the weight loss seen with licogliflozin by 12 weeks is promising.…”
Section: Discussionsupporting
confidence: 55%
“…inhibition, 37 and it is in line with the clinically meaningful weight loss of >5% (at 12 months) that is required by the FDA for approval of new drugs. 8 post-prandial glucose (incremental AUC reduced by >90%).…”
Section: Discussionmentioning
confidence: 59%
“…In terms of safety, all SGLT2 inhibitors have been associated with an elevated risk of genitourinary infections as a result of increased glycosuria . More seriously, the risk of diabetic ketoacidosis (DKA) has also been seen to increase , with an FDA warning applicable to all drugs of this class .…”
Section: Existing Sglt Inhibitors For Diabetes Mellitusmentioning
confidence: 99%
“…However, heterogeneous study designs and variable participant characteristics mean that results should be interpreted with caution. In terms of safety, all SGLT2 inhibitors have been associated with an elevated risk of genitourinary infections as a result of increased glycosuria [28,31]. More seriously, the risk of diabetic ketoacidosis (DKA) has also been seen to increase [25,[32][33][34], with an FDA warning applicable to all drugs of this class [35][36][37].…”
Section: What's New?mentioning
confidence: 99%
“…Studies indicate that sotagliflozin could reduce insulin resistance and may be a valuable adjunct for metformin and DPP‐4 inhibitors in patients with T2DM. Additional benefits include reductions in weight, systolic blood pressure, and appetite, and benefits for individuals with reduced kidney function were also noted (Rosenstock et al, ; Wang, Hu, Liu, & Wang, ). Sotagliflozin has entered into phase III trials to treat patients with T1DM and has shown promising outcomes (DANNE et al, ).…”
Section: Phlorizinmentioning
confidence: 94%